Contract management for dredging and maritime construction delegate information : 12-13 October 2006 : venue, Hilton Docklands, London, UK. (Thomas Telford, 2006)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in Docklands 12-13 October 2006.